Tantangan dan Solusi Pendidikan Islam di Era Digital: Menjaga Nilai Religius di Tengah Arus Modernisasi - Nayla Tiara Puspa; Syamsul Aripin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to analyze the challenges and solutions of Islamic education in the digital era in an effort to maintain religious values in the midst of the rapid flow of modernization and technological development. This research uses the library research method by examining various relevant literature sources, such as books, journals, and previous research results. The results of the study show that technological advances have a great influence on students' learning patterns, behaviors, and moral values. However, with the right strategy, technology can also be used as a means of da'wah and strengthening Islamic character. Efforts that need to be made include the integration of Islamic values in digital-based learning, improving teachers' competence in technological literacy, and collaboration between schools, families, and communities. This research emphasizes that Islamic education must be adaptive to the development of the times, but still adhere to religious values in order to produce a generation of Muslims who are intelligent, faithful, and noble. In addition, curriculum innovation that is responsive to the needs of the times and the use of safe and directed digital media is needed to support the formation of students' character comprehensively.